Neuromanagement as a Tool in Organizational Metamorphosis in Colombia (2017)
Introduction: This research intends to understand neuromanagement as a tool in organizational metamorphosis, revealing the brain arrangements to assume business change processes in the mining sector in the departments of La Guajira and Cesar, Colombia. Materials and methods: A postpositivist paradigm with a qualitative methodology was followed, based on the experiential introspection approach, according to the type of phenomenological research and some adaptations from behavioral sciences; it was designed in five stages that emerged from the theoretical construct of organizational metamorphosis. Case history: The intentional sample consisted of four individuals with a leadership role in the organizations. Results: A functional metamorphosis was noticed, and its results favored the evolution of the organizations and had a positive impact on the building of a new culture, in which the respect for the differences and the awareness of safety at work allowed the preservation of life. Conclusions: Evidently, it is necessary to make innovations by actively listening to the proposals of the organizations’ members for continuous improvement, in harmony with the humanized substance of the being.